Teaching EIL – teaching international or intercultural English: What teachers should know - Sifakis, N. (System, 2004)
The article concentrates on setting some specific criteria for the EIL (‘English as an international language’) classroom and raising teachers’ awareness of what is needed in order to identify and teach EIL classrooms. It starts by distinguishing between those communicative and teaching situations that are norm-bound and those that prioritise interlocutors’ mutual comprehensibility and cultural identity. On that basis, it goes on to delineate the EIL domain in norm-bound terms and suggests that teachers should also concentrate on teaching English as an intercultural language (EIcL). It subsequently addresses the following questions: What are the defining characteristics of an EIL/EIcL situation? How can a teacher identify such a situation and by what means can this be done? To what extent are EIL/EIcL situations similar to or different from other ESL, EFL, or more general ESOL situations? Are all EIL/EIcL situations around the world the ‘same’ and, if not, to what extent are they similar/different? To what extent do learners’ and teachers’ attitudes towards English, language learning and their own national, cultural and personal identity matter in EIL/EIcL learning/teaching?